2016
DOI: 10.1039/c6ra14678c
|View full text |Cite
|
Sign up to set email alerts
|

Carbonylative coupling of aryl tosylates/triflates with arylboronic acids under CO atmosphere

Abstract: The carbonylative Suzuki–Miyaura reaction between aryl tosylates/triflates with arylboronic acid is herein reported, using base-free conditions and a balloon pressure of carbon monoxide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…Chang and his research group [51] has reported the same coupling reaction without using any base and balloon pressure of CO gas as the source of carbonyl group. However, they have employed aryl triflates 41b or tosylates 41a along with arylboronic acids 41c as coupling partners.…”
Section: Palladium Catalysed Carbonylative Suzuki‐miyaura Coupling Rementioning
confidence: 85%
“…Chang and his research group [51] has reported the same coupling reaction without using any base and balloon pressure of CO gas as the source of carbonyl group. However, they have employed aryl triflates 41b or tosylates 41a along with arylboronic acids 41c as coupling partners.…”
Section: Palladium Catalysed Carbonylative Suzuki‐miyaura Coupling Rementioning
confidence: 85%
“…[67] However,c ross-coupling of 18 with ap henyls ilane in the presence of aP ,N ligand (39)l eads to preferentialr eactiona tt osylate (Scheme 25 B). [68] Selectivity has also been reported in af ew other lesst raditional couplings of chlorophenyl tosylate 18.F or example, 18 undergoes tosylate-selective reaction in aP d/dppe-catalyzed carbonylative Suzukic oupling, [69] aP d/dppf-catalyzed reductive homocoupling, [70] and aP d/dppf-catalyzed decarboxylative coupling with an a,b-unsaturated carboxylic acid. [71] The different chemoselectivities of the Pd-catalyzedc rosscouplings discussed so far in this section have not been systematically studied or explained.…”
Section: Chloride Vs Tosylatementioning
confidence: 88%
“…Selectivity has also been reported in a few other less traditional couplings of chlorophenyl tosylate 18 . For example, 18 undergoes tosylate‐selective reaction in a Pd/dppe‐catalyzed carbonylative Suzuki coupling, [69] a Pd/dppf‐catalyzed reductive homocoupling, [70] and a Pd/dppf‐catalyzed decarboxylative coupling with an α,β‐unsaturated carboxylic acid [71]…”
Section: Divergent Selectivity Between a Halide And A Pseudohalidementioning
confidence: 99%
“…Goossen et al [40] accomplished similar PdBr 2 /CuBr-catalyzed decarboxylative reaction under ligand-free conditions at 170°C in a 79% yield (Scheme 1, equation (2)). [44][45][46][47][48] The use of phenol derivatives instead of halides reduces the production of halide waste, thus lowering the environmental impact of the cross-coupling process. A yield of 82% of (E)-1-methyl-4-styrylbenzene was obtained under catalysis of PdBr 2 /CuF 2 with (o-biphenyl)PtBu 2 at 170°C (Scheme 1, equation (3)).…”
Section: Introductionmentioning
confidence: 99%
“…SCHEME 1 Pd-catalyzed decarboxylative cross-coupling of cinnamic acids with various coupling partners Oxygen-based electrophiles have frequently been employed as (pseudo)aryl halides in transition metalcatalyzed coupling reactions because they are easily prepared from phenol derivatives, which are inexpensive and readily accessible compared to aryl halides. [44][45][46][47][48] The use of phenol derivatives instead of halides reduces the production of halide waste, thus lowering the environmental impact of the cross-coupling process. Furthermore, the use of phenol derivatives may exhibit orthogonal reactivity to aryl halides.…”
Section: Introductionmentioning
confidence: 99%